Brazilian Expert Consensus for NTRK Gene Fusion Testing in Solid Tumors - Mariana Petaccia de Macedo; Ellen Caroline Toledo Nascimento; Fernando Augusto Soares; Fernando Costa Santini; Felipe D’Almeida Costa; Isabela Werneck da Cunha; Rodrigo Ramella Munhoz; Pedro De Marchi; Thiago William Carnier Jorge; Kátia Ramos Moreira Leite (Clinical Pathology, 2023)
Oncogenic neurotrophic tropomyosin receptor kinase gene fusions occur in less than 1% of common cancers. These mutations have emerged as new biomarkers in cancer genomic profiling with the approval of selective drugs against tropomyosin receptor kinase fusion proteins. Nevertheless, the optimal pathways and diagnostic platforms for this biomarker’s screening and genomic profiling have not been defined and remain a subject of debate. A panel of national experts in molecular cancer diagnosis and treatment was convened by videoconference and suggested topics to be addressed in the literature review. The authors proposed a testing algorithm for oncogenic neurotrophic tropomyosin receptor kinase gene fusion screening and diagnosis for the Brazilian health system. This review aims to discuss the latest literature evidence and international consensus on neurotrophic tropomyosin receptor kinase gene fusion diagnosis to devise clinical guidelines for testing this biomarker. We propose an algorithm in which testing for this biomarker should be requested to diagnose advanced metastatic tumors without known driver mutations. In this strategy, Immunohistochemistry should be used as a screening test followed by confirmatory next-generation sequencing in immunohistochemistry-positive cases.